2011
DOI: 10.3168/jds.2010-4056
|View full text |Cite
|
Sign up to set email alerts
|

Starch source and content in postpartum dairy cow diets: Effects on plasma metabolites and reproductive processes

Abstract: The objective of this study was to examine the effects of dietary starch source and content in the immediate postpartum period on plasma metabolites and hormones and ovarian follicular development. One of 3 diets was fed in a randomized block design to 40 cows from calving until 70 d in milk. The diets contained 45% alfalfa silage (AS), 45% barley silage (BS), or 41% barley silage and 4% supplemental starch (SS) on a dry matter basis. All diets contained 45% barley-based concentrate and 10% alfalfa hay. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
5
15
3
Order By: Relevance
“…In subsequent research, the number of cows pregnant at 120 days was greater for cows fed a glucogenic (high-starch) diet that increased insulin early postpartum followed by the lipogenic diet (higher fat) during the breeding period (Garnsworthy et al, 2009). More recent studies have not confirmed this effect (Dyck et al, 2011;Gilmore et al, 2011) although diets and experimental conditions differed and cow numbers were limited. The aim to increase early postpartum insulin by feeding higher starch diets must be tempered by the need to maintain optimal rumen health and digestion.…”
Section: Postpartum (Fresh Cow) Dietary Considerationsmentioning
confidence: 95%
“…In subsequent research, the number of cows pregnant at 120 days was greater for cows fed a glucogenic (high-starch) diet that increased insulin early postpartum followed by the lipogenic diet (higher fat) during the breeding period (Garnsworthy et al, 2009). More recent studies have not confirmed this effect (Dyck et al, 2011;Gilmore et al, 2011) although diets and experimental conditions differed and cow numbers were limited. The aim to increase early postpartum insulin by feeding higher starch diets must be tempered by the need to maintain optimal rumen health and digestion.…”
Section: Postpartum (Fresh Cow) Dietary Considerationsmentioning
confidence: 95%
“…In contrast, other investigations found no or negative effects of the energy intake level on the conception rate following the first insemination (McNamara et al, 2003;Garnsworthy et al, 2009;Gilmore et al, 2011). Furthermore, some studies found improved pregnancy rates when feeding dietary starch or fat to dairy cows (Burke et al, 2010;Reis et al, 2012), while others reported no or negative effects (McNamara et al, 2003;Dyck et al, 2011;Gilmore et al, 2011). However, important enhancements in conception rates were observed when feeding a diet that increased glucose and insulin levels in the early postpartum period and then switching to a diet that reduced insulin levels during the mating period, compared with other treatments (Garnsworthy et al, 2009).…”
Section: Effect Of Energy Sources On Reproductive Efficiency Of Dairymentioning
confidence: 71%
“…Manipulating the energy level and source in the diet of pre-and postpartum cows showed significant improvements in terms of decreased incidence of health problems (Beever, 2006), optimized rumen microbial activity (Jouany, 2006), increased amount of digested nutrients from the gastro-intestinal tract (GIT) (Bauman & Currie, 1980), decreased body condition loss (Drehmann, 2000;Butler, 2003), and increased milk responses (Grum et al, 1996;Ingvartsen & Andersen, 2000;Cavestany et al, 2009a;Reis et al, 2012;Damgaard et al, 2013;Roche et al, 2013;Hills et al, 2015). However, studies on the pre-and postpartum effects of starch-or fat-based diets on dairy cow reproduction parameters are contradictory, with some studies reporting a negative effect or lack of effect of it (Beam & Butler, 1997;Oldick et al, 1997;Oldick et al, 1998;McNamara et al, 2003;Van Knegsel et al, 2007c;Dyck et al, 2011;Gilmore et al, 2011), compared with other studies that reported a positive effect (Gong et al, 2002;Cavestany et al, 2009b;Garnsworthy et al, 2009;Reis et al, 2012;Little et al, 2016;Thatcher, 2017). The objectives of this review are therefore to discuss the effects of energy-based diets containing starch and/or fat during the dry and postpartum periods on the subsequent metabolism, milk production and fertility of dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Rizos et al (18) showed that the maximum follicle sizes in the first follicular waves after parturition were, on average, 16.8 mm and 18.3 mm in high-energy and control groups, respectively, and differences were found to be insignificant. In one study, Dyck et al (19) found that the maximum follicle size in the first follicular wave was approximately 17.5 mm, and different dietary starch levels (these were 23.3%, 25.2%, and 26.7% in the groups in the study) did not affect ovarian dynamics. We found a smaller maximum follicle size in the first follicular wave than these studies, with no differences among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although many factors affect the resumption of postpartum cyclicity, the maximum follicular size in the first follicular wave is important to the onset of cyclicity in dairy cows. The size and ability of the first dominant follicle to ovulate postpartum are the decisive factors (7,19). It is known that the ovulatory follicle size must be greater than 10 mm (7,16).…”
Section: Discussionmentioning
confidence: 99%